Corrosion-resistant pure magnetic porous foam wave-absorbing material and preparation method thereof

The corrosion-resistant pure magnetic porous foam absorbing materials are prepared by liquid nitrogen directed freezing and ammonia nitriding, which solves the problems of complex preparation and easy corrosion of existing absorbing materials, and achieves high-efficiency electromagnetic wave absorption and corrosion resistance.

CN119603946AActive Publication Date: 2025-03-11ZHEJIANG UNIV OF TECH
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202411689015.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing wave absorbing materials have complex preparation processes, which may lead to local magnetic field inhomogeneity and low electromagnetic wave loss, and are prone to corrosion, which cannot meet the application needs in complex environments.

Method used

Corrosion-resistant pure magnetic porous foam absorbing materials are prepared by liquid nitrogen directed freezing and ammonia nitriding methods, and iron tetranidae porous foam material is generated by oriented freezing and calcining of hydroxy iron oxide nanowire materials.

Benefits of technology

The corrosion resistance and efficient electromagnetic wave absorption performance of the material are achieved, the preparation process is simplified, and the ferromagnetic performance and electromagnetic wave loss capability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119603946A_ABST
    Figure CN119603946A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant pure magnetic porous foam wave-absorbing material and a preparation method thereof, and relates to the technical field of electromagnetic wave absorbing materials. According to the method, ferric hydroxide precipitate is subjected to a hydrothermal reaction to generate a ferric hydroxide one-dimensional nanowire, then the one-dimensional nanowire serves as a matrix, a porous foam material is prepared in a liquid nitrogen directional freezing and vacuum drying mode, and the corrosion-resistant pure magnetic porous foam wave-absorbing material is finally obtained through calcination in an ammonia atmosphere. According to the invention, orientation freezing is carried out by using ultralow-temperature liquid nitrogen, and then the foam material with a porous structure in specific orientation arrangement is successfully prepared through vacuum drying, so that electromagnetic waves can penetrate into the material along the pores, and more electromagnetic wave energy is converted into heat energy to be dissipated; and higher electromagnetic wave absorption performance can be realized. In addition, calcination is carried out in the ammonia atmosphere, no organic matter needs to be added, and the iron tetranitrogen pure magnetic porous foam material is finally obtained and shows higher corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials, and in particular relates to a corrosion-resistant pure magnetic porous foam absorbing material and a preparation method thereof. Background Art

[0002] With the continuous advancement of science and technology, electronic information equipment has been widely used in civilian and military fields. Since the electromagnetic waves emitted by these devices pose a potential threat to the natural environment and human health, people have developed absorbing materials that can absorb electromagnetic waves. However, traditional absorbing materials often have characteristics such as light weight, large absorption bandwidth, high reflection loss, and thin matching thickness. When some electronic equipment is used in complex environments, traditional absorbing materials can no longer meet the wide application needs in complex environments. Therefore, improving the environmental stability of absorbing materials has become the focus of current research, which has led to the emergence of corrosion-resistant materials. Applying this material with corrosion-resistant characteristics to electronic equipment in special environments can not only effectively absorb electromagnetic waves, but also extend the service life of the absorbing material.

[0003] A Chinese patent with application number CN202311017696.4 discloses a magnetic composite corrosion-resistant absorbing material, which is a core-shell structure, wherein the core is a magnetic micropowder and the shell is an inorganic inner shell / organic silicon polymer outer shell. The inorganic inner shell is SiO2, and the organosilicon polymer outer shell is polymerized from 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane (F13) and methyltrimethoxysilane (MTMS). The magnetic composite corrosion-resistant absorbing material has good reflection loss and large absorption bandwidth, as well as good corrosion resistance.

[0004] In the above technical solution, by constructing a core-shell structure of magnetic core and non-magnetic shell, although the corrosion resistance and microwave absorption performance of the material are enhanced, the following problems exist: (1) The preparation process of the magnetic composite core-shell material is relatively complicated; (2) The magnetic composite core-shell material may cause local magnetic field inhomogeneity problems, thereby reducing the ferromagnetic properties of the material; (3) The core-shell structure cannot allow more electromagnetic waves to enter the interior of the material, so that more electromagnetic wave energy cannot be converted into heat and dissipated, which will result in less electromagnetic wave loss.

[0005] Therefore, it is of great significance to prepare porous foam absorbing materials with excellent corrosion resistance and pure magnetic characteristics through a simple process. Summary of the invention

[0006] The first purpose of the present invention is to address the deficiencies of the prior art and propose a method for preparing a corrosion-resistant pure magnetic porous foam absorbing material, which is completed by liquid nitrogen directional freezing and ammonia nitriding, and combined with the material's own characteristics and inherent magnetic properties and crystal structure characteristics to obtain a corrosion-resistant electromagnetic wave absorbing material. This solves the current problems of complex preparation processes, mostly composite materials, less electromagnetic wave loss, and easy corrosion of absorbing materials.

[0007] To achieve the purpose of the present invention, the present invention is implemented by the following technical solutions:

[0008] A method for preparing a corrosion-resistant pure magnetic porous foam absorbing material comprises the following steps:

[0009] Step (1), preparation of ferric hydroxide precipitate

[0010] The ferric chloride hexahydrate and sodium hydroxide are dissolved and mixed respectively, and potassium hydroxide is added to prepare an iron hydroxide precipitate in an alkaline environment;

[0011] Step (2): Preparation of one-dimensional iron oxyhydroxide nanowires

[0012] The iron hydroxide precipitate is subjected to a hydrothermal reaction to obtain one-dimensional iron oxyhydroxide nanowires;

[0013] Step (3), preparation of porous iron oxyhydroxide foam material

[0014] The one-dimensional iron oxyhydroxide nanowires are dissolved in deionized water, oriented and frozen using ultra-low temperature liquid nitrogen, and then vacuum dried to obtain an iron oxyhydroxide porous foam material;

[0015] Step (4): Preparation of corrosion-resistant pure magnetic porous foam absorbing material

[0016] The porous iron oxyhydroxide foam material is placed in an ammonia atmosphere for calcination. Under the action of reducing hydrogen and nitrogen atoms, the porous iron oxyhydroxide foam material undergoes a chemical reaction to generate an iron tetranitrogen porous foam material, namely the corrosion-resistant pure magnetic porous foam wave absorbing material.

[0017] Preferably, in step (1), the weight proportion of ferric chloride hexahydrate is 1-4 parts, the weight proportion of sodium hydroxide is 3-12 parts, and the weight proportion of potassium hydroxide is 6-10 parts.

[0018] Preferably, in step (1), the weight portion of ferric chloride hexahydrate is 1 part, the weight portion of sodium hydroxide is 3 parts, and the weight portion of potassium hydroxide is 6 parts.

[0019] Preferably, in step (1), the weight parts of ferric chloride hexahydrate are 4 parts, the weight parts of sodium hydroxide are 12 parts, and the weight parts of potassium hydroxide are 8 parts.

[0020] Preferably, the hydrothermal temperature in step (2) is 90-120°C.

[0021] Preferably, the reaction time in step (2) is 15-20 h.

[0022] Preferably, the temperature of the ultra-low temperature liquid nitrogen in step (3) is -197°C.

[0023] Preferably, the drying time in step (3) is 12-48 hours.

[0024] Preferably, the calcination temperature in step (4) is 300-400°C.

[0025] Preferably, the calcination time in step (4) is 2-6 hours.

[0026] In the present invention, ultra-low temperature liquid nitrogen is used for directional freezing. Compared with conventional freezing methods, liquid nitrogen freezing can more freely select the direction of ice crystal growth, thereby achieving the purpose of directional freezing of samples; the present invention also uses an ammonia atmosphere for calcination. Compared with a nitrogen atmosphere, nitrogen is not easy to decompose nitrogen atoms, and uneven nitridation is prone to occur; while an ammonia atmosphere can decompose nitrogen atoms and reducing hydrogen at high temperatures, and the generated reducing hydrogen reduces hydroxyl iron oxide, and the generated reducing substances are then nitrided under the influence of surrounding nitrogen atoms, and finally a pure iron tetranitrogen phase is obtained.

[0027] The second object of the present invention is to provide a corrosion-resistant pure magnetic porous foam absorbing material, which is prepared by the above method.

[0028] The present invention provides a corrosion-resistant pure magnetic porous foam wave absorbing material. It has the following beneficial effects:

[0029] (1) The present invention uses iron oxyhydroxide nanowire material as a matrix and uses ultra-low temperature liquid nitrogen for orientation freezing, thereby precisely controlling the growth direction of ice crystals. Subsequently, a foam material with a porous structure with a specific orientation arrangement is successfully prepared by vacuum drying. This material combines the porous characteristics, allowing electromagnetic waves to penetrate into the material along these pores, converting more electromagnetic wave energy into heat energy and dissipating it, which is conducive to achieving higher electromagnetic wave absorption performance.

[0030] (2) The present invention uses ammonia as a reducing atmosphere to calcine the iron oxyhydroxide porous foam material at 300-400°C without adding any organic matter, and finally obtains a pure magnetic porous foam material of iron tetrazolybdenum. This pure magnetic material does not contain impurities, can effectively absorb and attenuate electromagnetic waves, and compared with conventional carbonyl iron powder materials, it exhibits stronger corrosion resistance, thereby realizing the effective application of the absorbing material in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the steps of the preparation method of the present invention.

[0032] Figure 2 This is the surface morphology of the porous iron oxyhydroxide foam material obtained by liquid nitrogen freezing under an optical microscope.

[0033] Figure 3 This is the surface morphology of the porous iron oxyhydroxide foam material obtained by freezing in a freeze dryer under an optical microscope.

[0034] Figure 4 This is an electron microscope image of the microstructure of the corrosion-resistant pure magnetic porous foam material of Example 1 at 800 times.

[0035] Figure 5 This is an electron microscope image of the microstructure of the corrosion-resistant pure magnetic porous foam material of Example 1 at 3200 times. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be described in detail below in conjunction with the embodiments and illustrations of the present invention. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0037] The raw materials used in the following examples were all obtained through conventional commercial routes.

[0038] like Figure 1 As shown, the present invention provides a method for preparing a corrosion-resistant pure magnetic porous foam absorbing material, comprising the following steps:

[0039] Step (1), preparation of one-dimensional iron oxyhydroxide nanowires

[0040] Dissolving 1-4 parts by weight of ferric chloride hexahydrate and 3-12 parts by weight of sodium hydroxide respectively and mixing them, and then adding 6-10 parts by weight of potassium hydroxide to prepare an iron hydroxide precipitate under an alkaline environment; placing the iron hydroxide precipitate in an oven at 90-120° C. for hydrothermal reaction for 15-20 hours to obtain one-dimensional iron oxyhydroxide nanowires;

[0041] Step (2), preparation of porous iron oxyhydroxide foam material

[0042] The one-dimensional iron oxyhydroxide nanowires are dissolved in deionized water, oriented and frozen using ultra-low temperature liquid nitrogen (-197°C), and then vacuum dried for 12-48 hours to obtain an iron oxyhydroxide porous foam material;

[0043] Step (3): Preparation of corrosion-resistant pure magnetic porous foam absorbing material

[0044] The porous iron oxyhydroxide foam material is placed in an ammonia atmosphere and calcined at 300-400°C for 2-6 hours. The porous iron oxyhydroxide foam material undergoes a chemical reaction under the action of reducing hydrogen and nitrogen atoms to generate an iron tetranitrogen porous foam material, thereby obtaining the corrosion-resistant pure magnetic porous foam absorbing material.

[0045] In the above preparation process, the amount of each raw material, the reaction time and the reaction temperature can be selected according to actual needs. For example, in some embodiments, the weight of ferric chloride hexahydrate is 1-4 parts, which can be specifically selected from 1 part, 2 parts, 3 parts, and 4 parts; the weight of sodium hydroxide is 3-12 parts, which can be specifically selected from 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, and 12 parts; the weight of potassium hydroxide is 6-10 parts, which can be specifically selected from 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts; the oven temperature is 90-120°C, which can be specifically selected from 90°C, 95°C, 100°C, 105 ℃, 110℃, 115℃, 120℃; hydrothermal reaction time is 15-20h, specifically can be selected from 15h, 16h, 17h, 18h, 19h, 20h; vacuum drying time is 12-48h, specifically can be selected from 12h, 24h, 36h, 48h; calcination temperature in ammonia atmosphere is 300-400℃, specifically can be selected from 300℃, 320℃, 340℃, 360℃, 380℃, 400℃; calcination time is 2-6h, specifically can be selected from 2h, 3h, 4h, 5h, 6h; in addition to the above-mentioned exemplified values, it can also be any value within the range, which is not limited here.

[0046] The present invention is further described below in conjunction with specific embodiments.

[0047] Example 1

[0048] A method for preparing a corrosion-resistant pure magnetic porous foam absorbing material comprises the following steps:

[0049] Step 1: Preparation of iron hydroxide precipitate

[0050] 1 part of ferric chloride hexahydrate and 3 parts of sodium hydroxide were dissolved in deionized water and mixed with each other to form ferric hydroxide precipitate, and then 6 parts of potassium hydroxide were added to construct an alkaline environment.

[0051] Step 2: Preparation of one-dimensional iron oxyhydroxide nanowires

[0052] The mixed solution containing the iron hydroxide precipitate obtained in step 1 was stirred, and then placed in an oven at 120° C. for 18 hours of hydrothermal treatment to obtain a one-dimensional iron oxyhydroxide nanowire material.

[0053] Step 3: Preparation of porous iron oxyhydroxide foam structure

[0054] The one-dimensional nanowire material prepared in step 2 was mixed with deionized water in a ratio of 1:2, poured into a constant container, and freeze-dried using liquid nitrogen at -197°C. The frozen sample was vacuum dried for 12 hours. The purpose of drying was to volatilize ice crystals and produce a porous structure, and finally a porous iron oxyhydroxide foam material was obtained. Figure 2 This is a surface morphology of the porous iron oxyhydroxide foam material obtained by liquid nitrogen freezing in this example under an optical microscope.

[0055] Step 4: Preparation of Fe-Tetranitrogen Corrosion-Resistant Pure Magnetic Porous Foam Material

[0056] The iron oxyhydroxide porous foam material prepared in step three is placed in a tubular furnace and nitrided with 95% pure ammonia for 6 hours at 300°C to obtain corrosion-resistant iron tetranitride and ultimately obtain a corrosion-resistant pure magnetic porous foam material.

[0057] Figure 4 and 5 is a microstructure diagram of this embodiment, wherein Figure 4 This is an electron microscope image at 800 times magnification. Figure 5 This is an electron microscope image at 3200 times magnification.

[0058] Example 2

[0059] A method for preparing a corrosion-resistant pure magnetic porous foam absorbing material comprises the following steps:

[0060] Step 1: Preparation of iron hydroxide precipitate

[0061] 2 parts of ferric chloride hexahydrate and 6 parts of sodium hydroxide were dissolved in deionized water and mixed with each other to form ferric hydroxide precipitate, and then 7 parts of potassium hydroxide were added to construct an alkaline environment.

[0062] Step 2: Preparation of one-dimensional iron oxyhydroxide nanowires

[0063] The mixed solution containing the iron hydroxide precipitate obtained in step 1 was stirred, and then placed in an oven at 120° C. for 18 hours of hydrothermal treatment to obtain a one-dimensional iron oxyhydroxide nanowire material.

[0064] Step 3: Preparation of porous iron oxyhydroxide foam structure

[0065] The one-dimensional nanowire material prepared in step 2 was mixed with deionized water in a ratio of 1:2, poured into a constant container, freeze-dried using liquid nitrogen at -197°C, and the frozen sample was vacuum dried for 16 hours to finally obtain a porous iron oxyhydroxide foam material.

[0066] Step 4: Preparation of Fe-Tetranitrogen Corrosion-Resistant Pure Magnetic Porous Foam Material

[0067] The iron oxyhydroxide porous foam material prepared in step 3 is placed in a tubular furnace and nitrided with 95% pure ammonia for 5 hours at 320° C. to finally obtain a corrosion-resistant pure magnetic porous foam material.

[0068] In this embodiment, the remaining parameters are the same as those in Embodiment 1.

[0069] Example 3

[0070] A method for preparing a corrosion-resistant pure magnetic porous foam absorbing material comprises the following steps:

[0071] Step 1: Preparation of iron hydroxide precipitate

[0072] 4 parts of ferric chloride hexahydrate and 12 parts of sodium hydroxide were dissolved in deionized water and mixed with each other to form ferric hydroxide precipitate, and then 10 parts of potassium hydroxide were added to construct an alkaline environment.

[0073] Step 2: Preparation of one-dimensional iron oxyhydroxide nanowires

[0074] The mixed solution containing the iron hydroxide precipitate obtained in step 1 was stirred, and then placed in an oven at 120° C. for 18 hours of hydrothermal treatment to obtain a one-dimensional iron oxyhydroxide nanowire material.

[0075] Step 3: Preparation of porous iron oxyhydroxide foam structure

[0076] The one-dimensional nanowire material prepared in step 2 was mixed with deionized water in a ratio of 1:2, poured into a constant container, freeze-dried using liquid nitrogen at -197°C, and the frozen sample was vacuum dried for 24 hours to finally obtain a porous iron oxyhydroxide foam material.

[0077] Step 4: Preparation of Fe-Tetranitrogen Corrosion-Resistant Pure Magnetic Porous Foam Material

[0078] The porous iron oxyhydroxide material prepared in step 3 is placed in a tubular furnace and nitrided with 95% pure ammonia for 2 hours at 400° C. to finally obtain a corrosion-resistant pure magnetic porous foam material.

[0079] In this embodiment, the remaining parameters are the same as those in Embodiment 1.

[0080] In combination with Example 1, Example 2 and Example 3, in the present invention, a corrosion-resistant pure magnetic porous foam absorbing material is used, with iron oxyhydroxide nanowires as the matrix, and ultra-low temperature liquid nitrogen is used for oriented freezing, and the direction of ice crystal growth is controlled to obtain an oriented porous structure. Combined with the porous characteristics, electromagnetic waves can penetrate into the material along these pores, and more electromagnetic wave energy is converted into heat energy for dissipation, which is conducive to achieving higher electromagnetic wave absorption performance. At the same time, in the present invention, a single-phase pure magnetic iron tetranitrogen compound is obtained by calcining in an ammonia atmosphere, which increases the corrosion resistance of the porous foam absorbing material.

[0081] Comparative Example 1: Hydrogen is used as the reducing atmosphere

[0082] In this comparative example, a pure magnetic ferroferric oxide porous foam absorbing material is prepared, comprising the following steps:

[0083] Step 1: Preparation of iron hydroxide precipitate

[0084] 1 part of ferric chloride hexahydrate and 3 parts of sodium hydroxide were dissolved in deionized water and mixed with each other to form ferric hydroxide precipitate, and then 6 parts of potassium hydroxide were added to construct an alkaline environment.

[0085] Step 2: Preparation of one-dimensional iron oxyhydroxide nanowires

[0086] The mixed solution containing the iron hydroxide precipitate obtained in step 1 was stirred, and then placed in an oven at 120° C. for 18 hours of hydrothermal treatment to obtain a one-dimensional iron oxyhydroxide nanowire material.

[0087] Step 3: Preparation of porous iron oxyhydroxide foam structure

[0088] The one-dimensional nanowire material prepared in step 2 was mixed with deionized water in a ratio of 1:2, poured into a constant container, and freeze-dried using liquid nitrogen at -197°C. The frozen sample was vacuum dried for 12 hours. The purpose of drying was to volatilize ice crystals and produce a porous structure, and finally a porous iron oxyhydroxide foam material was obtained.

[0089] Step 4: Preparation of pure magnetic porous ferroferric oxide foam material

[0090] The porous iron oxyhydroxide foam material prepared in step three is placed in a tubular furnace and reduced with hydrogen at 300° C. for 5 hours, in order to obtain a pure magnetic porous iron oxide foam material.

[0091] Comparative Example 2: Hydrogen is used as the reducing atmosphere

[0092] In this comparative example, a pure magnetic iron and ferroferric oxide porous foam absorbing material is prepared, comprising the following steps:

[0093] Step 1: Preparation of iron hydroxide precipitate

[0094] 1 part of ferric chloride hexahydrate and 3 parts of sodium hydroxide were dissolved in deionized water and mixed with each other to form ferric hydroxide precipitate, and then 6 parts of potassium hydroxide were added to construct an alkaline environment.

[0095] Step 2: Preparation of one-dimensional iron oxyhydroxide nanowires

[0096] The mixed solution containing the iron hydroxide precipitate obtained in step 1 was stirred, and then placed in an oven at 120° C. for 18 hours of hydrothermal treatment to obtain a one-dimensional iron oxyhydroxide nanowire material.

[0097] Step 3: Preparation of porous iron oxyhydroxide foam structure

[0098] The one-dimensional nanowire material prepared in step 2 was mixed with deionized water in a ratio of 1:2, poured into a constant container, and freeze-dried using liquid nitrogen at -197°C. The frozen sample was vacuum dried for 12 hours. The purpose of drying was to volatilize ice crystals and produce a porous structure, and finally a porous iron oxyhydroxide foam material was obtained.

[0099] Step 4: Preparation of pure magnetic porous foam materials of iron and ferroferric oxide

[0100] The porous iron oxyhydroxide foam material prepared in step 3 is placed in a tubular furnace and reduced with hydrogen at 300° C. for 6 hours, in order to obtain a pure magnetic porous foam material of iron and ferroferric oxide.

[0101] Comparative Example 3: Reducing atmosphere using hydrogen and nitrogen

[0102] In this comparative example, a pure magnetic iron porous foam absorbing material is prepared, comprising the following steps:

[0103] Step 1: Preparation of iron hydroxide precipitate

[0104] 1 part of ferric chloride hexahydrate and 3 parts of sodium hydroxide were dissolved in deionized water and mixed with each other to form ferric hydroxide precipitate, and then 6 parts of potassium hydroxide were added to construct an alkaline environment.

[0105] Step 2: Preparation of one-dimensional iron oxyhydroxide nanowires

[0106] The mixed solution containing the iron hydroxide precipitate obtained in step 1 was stirred, and then placed in an oven at 120° C. for 18 hours of hydrothermal treatment to obtain a one-dimensional iron oxyhydroxide nanowire material.

[0107] Step 3: Preparation of porous iron oxyhydroxide foam structure

[0108] The one-dimensional nanowire material prepared in step 2 was mixed with deionized water in a ratio of 1:2, poured into a constant container, and freeze-dried using liquid nitrogen at -197°C. The frozen sample was vacuum dried for 12 hours. The purpose of drying was to volatilize ice crystals and produce a porous structure, and finally a porous iron oxyhydroxide foam material was obtained.

[0109] Step 4: Preparation of pure magnetic porous foam materials of iron and iron tetrazolybdenum

[0110] The porous iron oxyhydroxide foam material prepared in step 3 is placed in a tubular furnace and calcined in hydrogen and nitrogen at 300° C. for 8 h, in order to obtain pure magnetic porous iron and iron tetranitrogen foam materials.

[0111] Comparative Example 4: Preparation of porous iron oxyhydroxide foam material by conventional freezing method

[0112] Step 1: Preparation of iron hydroxide precipitate

[0113] 1 part of ferric chloride hexahydrate and 3 parts of sodium hydroxide were dissolved in deionized water and mixed with each other to form ferric hydroxide precipitate, and then 6 parts of potassium hydroxide were added to construct an alkaline environment.

[0114] Step 2: Preparation of one-dimensional iron oxyhydroxide nanowires

[0115] The mixed solution containing the iron hydroxide precipitate obtained in step 1 was stirred, and then placed in an oven at 120° C. for 18 hours of hydrothermal treatment to obtain a one-dimensional iron oxyhydroxide nanowire material.

[0116] Step 3: Preparation of porous iron oxyhydroxide foam structure

[0117] The one-dimensional nanowire material prepared in step 2 was mixed with deionized water in a ratio of 1:2, poured into a constant container, and freeze-dried using a freeze dryer for 12 hours. The purpose of drying was to volatilize ice crystals to produce a porous structure, and finally obtain a porous iron oxyhydroxide foam material.

[0118] The macroscopic morphology of the porous iron oxyhydroxide foam material prepared in this comparative example is as follows Figure 3 shown.

[0119] contrast Figure 2 and Figure 3 It can be found that after the sample is directional frozen by ultra-low temperature liquid nitrogen, the growth direction of the ice crystals can be precisely controlled, thereby obtaining a directional porous structure with a specific orientation arrangement that is more controllable than a freeze dryer.

[0120] The pure magnetic porous foam absorbing materials provided in the embodiment and comparative examples 1, 2 and 3 were measured using a vector network analyzer. The test results are shown in Table 1 below:

[0121] Table 1 Performance test results of pure magnetic porous foam absorbing materials

[0122]

[0123] As shown in the above table, the corrosion-resistant pure magnetic porous foam absorbing material provided by the present invention has excellent electromagnetic wave absorption properties.

[0124] Pure magnetic porous foam absorbing materials were provided for the embodiment and comparative examples 1, 2 and 3 for testing using an electrochemical workstation, and compared with a control group (the control group was carbonyl iron powder material purchased on the market, with a particle size of 1-2 μm and a purity of 99.99%). The test results are shown in Table 2 below:

[0125] Table 2 Corrosion resistance test results of pure magnetic porous foam absorbing materials

[0126]

[0127]

[0128] As shown in the above table, the corrosion potential of the iron tetranitrogen corrosion-resistant pure magnetic porous foam absorbing material obtained by the present invention is closer to a positive value, and exhibits better corrosion resistance than other pure magnetic porous foam materials and carbonyl iron powder materials.

[0129] The above embodiments are the basic principles, main features and advantages of the present invention. The present invention only illustrates the technical aspects and does not limit the protection scope of the present invention. Some improvements made according to the above embodiments are within the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant pure magnetic porous foam absorbing material, characterized in that: The preparation method comprises the following steps: Step (1), preparation of ferric hydroxide precipitate The ferric chloride hexahydrate and sodium hydroxide are dissolved and mixed respectively, and potassium hydroxide is added to prepare an iron hydroxide precipitate in an alkaline environment; Step (2): Preparation of one-dimensional iron oxyhydroxide nanowires The iron hydroxide precipitate is subjected to a hydrothermal reaction to obtain one-dimensional iron oxyhydroxide nanowires; Step (3), preparation of porous iron oxyhydroxide foam material The one-dimensional iron oxyhydroxide nanowires are dissolved in deionized water, oriented and frozen using ultra-low temperature liquid nitrogen, and then vacuum dried to obtain an iron oxyhydroxide porous foam material; Step (4): Preparation of corrosion-resistant pure magnetic porous foam absorbing material The iron oxyhydroxide porous foam material is placed in an ammonia atmosphere for calcination to obtain an iron tetranitrogen porous foam material, namely the corrosion-resistant pure magnetic porous foam wave absorbing material.

2. The method for preparing the corrosion-resistant pure magnetic porous foam absorbing material according to claim 1, characterized in that: In step (1), the weight proportion of ferric chloride hexahydrate is 1-4 parts, the weight proportion of sodium hydroxide is 3-12 parts, and the weight proportion of potassium hydroxide is 6-10 parts.

3. The method for preparing the corrosion-resistant pure magnetic porous foam absorbing material according to claim 1, characterized in that: The hydrothermal temperature in step (2) is 90-120°C.

4. The method for preparing the corrosion-resistant pure magnetic porous foam absorbing material according to claim 3, characterized in that: The reaction time in step (2) is 15-20h.

5. The method for preparing the corrosion-resistant pure magnetic porous foam absorbing material according to claim 1, characterized in that: The temperature of the ultra-low temperature liquid nitrogen in step (3) is -197°C.

6. The method for preparing the corrosion-resistant pure magnetic porous foam absorbing material according to claim 5, characterized in that: The drying time in step (3) is 12-48 hours.

7. The method for preparing the corrosion-resistant pure magnetic porous foam absorbing material according to claim 1, characterized in that: The calcination temperature in step (4) is 300-400°C.

8. The method for preparing the corrosion-resistant pure magnetic porous foam absorbing material according to claim 7, characterized in that: The calcination time in step (4) is 2-6 hours.

9. A corrosion-resistant pure magnetic porous foam absorbing material, prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Ferrite nano-pore microsphere wave-absorbing material and preparation method thereof

    CN103864408A

  • Polyurethane ferrite composite wave-absorbing porous material and preparation method thereof

    CN107868208A

  • Three-dimensional porous sheet ferroferric oxide / carbon nanometer electromagnetic wave absorption material and preparing method thereof

    CN108039257A

  • Porous ferroferric oxide / carbon nanometer rod-shaped electromagnetic wave absorbing material and preparing method and application thereof

    CN108154984A

  • A preparation method of a high-frequency microwave magnetic material

    CN108987088A